4D schedule generation for flat slab BIM models - Hosny, Amir Ossama (AUC Knowledge Fountain, 2017)
Planning & scheduling has made some amazing progress in the past 20 years, a period when numerous site engineers felt that utilizing formal planning was unnecessary to everyday operations and a period expending diversion. From that point forward, it has turned into a necessary piece for most projects, yet remains a period consuming, mistake inclined and manually initialized tool. This process is dependent on the method statements and the construction logic that are defined at the beginning of the project which will help in the development of the time schedule of works. Contractors use a set of defined productivity rates for the different construction activities that satisfy the required finish milestones specified by the contract; overcrowding and overmanning are not taken into considerations between labor in the project when selecting the productivity rates for the activities. Moreover, the site management team takes a huge amount of efforts and time to optimize the formwork area available and their reuse in different parts of the project. This research was divided into three stages; first stage was the collection of data stage which is mainly the interviews stage where interviews were held with about 14 experts. Second stage was the model was developed based on a number of algorithms to develop the time schedule and the cost estimation of a BIM model by minimum user inputs as well as including many parameters that are not being taken into considerations by planners in the contractors or the engineers side. Parameters include: the area of formwork available for construction in m2, the reuse of formwork in different zones for cost reduction, crowdedness and overmanning reduction for increase of productivity per crew, automatic zoning of building with relation to the construction joints in a building, optimization of number of crews and their allocation and the enhancement between the area of formwork available for construction and the number of crews. The model was validated with a case study project where the approved baseline schedule and the used method statement were compared to the model outputs. The results highlight the model's robust features in terms of: generating construction zones that account for the available amount of formwork and their reuse while minimizing the construction cost, optimizing the productivity rate per crew while considering the crowdedness of the job location per construction zone and over all optimizing the construction schedule in terms of time, cost and generating different method statement through formwork movements. Thus, using this model, a contractor could significantly improve his productivity, effectively generate construction schedules and method statements of a project.